Development of a Rabbit Model of Radiation-Induced Sciatic Nerve Injury. Issue 4 (July 2015) - Wan, Qi; Zeng, Qian; Li, Xinchun; Sun, Chongpeng; Zhou, Jiaxuan; Zou, Qiao; Deng, Yingshi; Niu, Daoli
<x xml:space="preserve">Abstract</x> Objectives To develop a rabbit model of radiation-induced sciatic nerve injury (RISNI), using computed tomography (CT)–guided stereotactic radiosurgery, and assess the value of T2 measurements of injured nerves. Materials and Methods Twenty New Zealand rabbits were randomly divided into A (n = 5) and B (n = 15) groups. Group A rabbits underwent CT and magnetic resonance scan and were then killed for comparison of images and anatomy of sciatic nerves. One side of the sciatic nerve of group B rabbits received irradiation doses of 35, 50, or 70 Gy (n = 5 per group). Magnetic resonance imaging and functional assessments were performed before irradiation and 1, 2, 3, and 4 months thereafter. Result The thigh section of the sciatic nerve outside the pelvis could be observed by CT and magnetic resonance imaging. T2 values of the irradiated nerve of the 35-Gy group increased gradually, peaking at 4 months; T2 values of the 50-Gy group increased faster, peaking at 3 months. Significant differences between the 35-Gy and control groups were found at 3 and 4 months, and between the 50-Gy and control groups at 2, 3, and 4 months. Functional scores of the 50-Gy group declined progressively, whereas the 35-Gy group scores reached a low point at 3 months posttreatment and then recovered. Functional scores of the irradiated limbs demonstrated a negative correlation with T2 values (r = −0.591 and −0.595, P < 0.05). Electron microscopy revealed progressive deformation and degeneration of the irradiated nerve in the 35- and 50-Gy groups, which were more severe in the 50-Gy group. Conclusions A rabbit RISNI model can be produced using the midthigh segment of the sciatic nerve and single-fraction doses of 35 and 50 Gy. Although T2 values are useful for monitoring RISNI, they may not be sensitive enough to evaluate its severity.